AI Powered Bioinformatics - Expediting Diagnostic Testing: A Survey - Rahaf Bajhzer,; Mona Alghamdi,; Salma Elhag, (International Journal of Computers and Informatics, 2024)
Research has demonstrated the positive impact of artificial intelligence and Bioinformatics in the field of clinical diagnosis. The integration of AI methodologies into bioinformatics has opened new avenues for breakthroughs in genomics, proteomics, and personalized medicine. The document emphasizes the role of AI in early disease detection, improving patient outcomes, and enhancing healthcare systems by avoiding the need for expensive and time-consuming operations as illnesses worsen. The methodology section provides insights into the approach utilized, including the review of 30 articles from highly regarded journals about AI and bioinformatics that expedite diagnostic testing in the medical field. using survey to gather information and divide it into sub-sections focusing on diagnostic cancer diseases, COVID-19, and genetic and chronic diseases. The survey gathered 52 responses, and the results revealed significant agreements with the findings in the papers, particularly in the importance of developing novel biosensors and diagnostic tools for rapid and accessible detection of SARS-CoV-2, and the potential of AI in laboratory settings, pharmaceutical industry, and disease diagnosis. Overall, the document provides a comprehensive overview of the transformative role of AI in bioinformatics, emphasizing its potential to revolutionize disease diagnosis, treatment, and public health decision-making, while also addressing the challenges and opportunities associated with the integration of AI technologies in the healthcare industry. The rigorous methodology and alignment of survey results with the research findings validate the significance of AI-powered bioinformatics in expediting diagnostic testing and improving patient safety in healthcare.
Keywords: Artificial Intelligence; Diagnosing; AI Powered Bioinformatics